Fermented Purple Sweet Potato in Rations on Carcass Improvement, Antioxidant Profile, Meat, and Eggs Lipid Profile of Bali Ducks - Yadnya, Tjokorda Gede Belawa; Sudana, Ida Bagus; Aryani, I.G. A.I. (Veterinary Science and Medicine Journal; Vol 4 No 1 (2016), 2016)
This study aimed to determine the effort of fermented purple sweet potato in the rations to improve carcass, antioxidant profile, meat and eggs lipid profile of bali ducks. Completely randomized design with three treatments was used in this study. Sixty baliducks were divided into 3 treatments that provision by rations; A: without purple sweet potato, B: with 10% purple sweet potato, C: with 10% fermented purple sweet potato.The experiment used four replications to each treatment which 5 layer ducks were used as a repetition in each unit of experiment. The experiment was done for 12 weeks. Antioxidant consumption was counted during the experiment. In the end of experiment the ducks were killed and meat antioxidant profile namely antioxidant capacity, malondialdehida (MDA) and superoxide dismutase (SOD), carcass profile including slaughter weight, carcass weight, carcass percentage, and physical carcass composition (meat, bone, fat including skin) were recorded. Meat and egg lipid profile (total cholesterol, highdensity lipoprotein (HDL), low density lipoprotein (LDL) and triglycerides) were also counted in the end of experiment.The results showed fermented purple sweet potato in the rations significantly increased the consumption of antioxidants, accompanied by increasing in slaughter weight, carcass weight, carcass percentage, and meat percentage. Fermented purple sweet potato in the rations also significantly reduced the percentage of sub-cutaneous fat and skin. Fermented purple sweet potato improved antioxidant profile significantly, increased antioxidant capacity, and superoxide dismutase (SOD), and decreased the levels of malondialdehid e (MDA). It also decreased significantly the total cholesterol, HDL, LDL and triglycerides in meat and eggs. The conclusion of the research is a 10 % fermented purple sweet potato in the rations be able to improve the antioxidant consumption, carcass, antioxidant profile, meat and eggs lipid profile of first laying phase of bali ducks.
Keywords: fermented purple sweet potato; antioxidant; meat and egg lipid profile; bali ducks